The Analysis of the Implementation of Sharia Accounting Standards (SAS) on the Application of PSAK 101 in the Financial Statements of PT. Bank Jabar Banten Syariah (BJB) - Ramlan, Peri; Suratminingsih; Was’an, Guruh Herman (Indonesian Journal Economic Review (IJER), 2025)
Islamic banks are financial institutions that conduct their operations based on Islamic Sharia principles. Essentially, an Islamic bank functions similarly to conventional banks in that it serves as a place to deposit funds and provide loans. All funds collected and disbursed for capital purposes are managed under a profit-sharing system. The dual banking system in Indonesia offers Muslims the opportunity to engage in financial transactions that comply with Shariah principles, specifically the profit-sharing model. The first Islamic bank was established in Egypt in 1963, known as the Mit Ghamr Local Saving Bank. Following this, other Islamic banks were established, including Dubai Islamic Bank in the UAE in 1975, Faysal Islamic Bank in Egypt and Sudan in 1977, and Kuwait Finance House in the same year. On November 1, 1991, the first Islamic bank in Indonesia, Bank Muamalat Indonesia, was founded. This bank operates according to Islamic Sharia principles and is considered a pioneer of Islamic banking in Indonesia. Islamic banks are expected to manage their financial activities in accordance with Islamic principles, particularly in their financial reporting. The current standard for financial reporting is PSAK 101. This study aims to investigate whether Islamic banks are adhering to these standards, as previous research has indicated discrepancies in the application of PSAK 101.